Mediators and Patterns of Muscle Loss in Chronic Systemic Inflammation - Pérez-Baos, Sandra; Prieto-Potin, Iván; Román-Blas, Jorge A.; Sánchez-Pernaute, Olga; Largo, Raquel; Herrero-Beaumont, Gabriel (Frontiers in Physiology, 2018)
Besides its primary function in locomotion, skeletal muscle (SKM), which represents up to half of human’s weight, also plays a fundamental homeostatic role. Through the secretion of soluble peptides, or myokines, SKM interacts with major organs involved in metabolic processes. In turn, metabolic cues from these organs are received by muscle cells, which adapt their response accordingly. This is done through an intricate intracellular signaling network characterized by the cross-talking between anabolic and catabolic pathways. A fine regulation of the network is required to protect the organism from an excessive energy expenditure. Systemic inflammation evokes a catabolic reaction in SKM known as sarcopenia. In turn this response comprises several mechanisms, which vary depending on the nature of the insult and its magnitude. In this regard, aging, chronic inflammatory systemic diseases, osteoarthritis and idiopathic inflammatory myopathies can lead to muscle loss. Interestingly, sarcopenia may persist despite remission of chronic inflammation, an issue which warrants further research. The Janus kinase/signal transducer and activator of transcription (JAK/STAT) system stands as a major participant in muscle loss during systemic inflammation, while it is also a well-recognized orchestrator of muscle cell turnover. Herein we summarize current knowledge about models of sarcopenia, their triggers and major mediators and their effect on both protein and cell growth yields. Also, the dual action of the JAK/STAT pathway in muscle mass changes is discussed. We highlight the need to unravel the precise contribution of this system to sarcopenia in order to design targeted therapeutic strategies.